Клиповость мышления и формирование межкультурной компетенции - Olga Makarowska (Studia Rossica Posnaniensia)
This article discusses the specifity of clip thinking. The article defines the concept and describes such primary features on cognitivistic level as drawbacks of this phenomenon. There were also proposed suggestions of small modifications used in process of forming intercultural comeptence for students studying Russian language on university level. On the one hand mentioned modification includes specificity of clip thinking, while on the second hand it is directed to such skills as analysis, synthesis, generalization etc.